The Effect of Reward Stamps in Encouraging Students’ Participation in Learning English - Faras Dwi Larasanti; Haryanto Atmowardoyo; Amra Ariyani (Program Studi Pendidikan Bahasa Inggris FBS UNM, 2026)
This study aims to determine the effect of reward stamps on students’ participation in learning English and to explore how they affect that participation. This study used an explanatory sequential mixed methods design conducted at UPTD SMAN 1 Polewali, involving 32 students as questionnaire respondents (18 statements) and 5 students as interview participants, selected using purposive random sampling techniques. The questionnaire analysis results show that most items are in the high category (55.6%), followed by the medium category (33.3%), and the very high category (11.1%), with no items in the low or very low categories, indicating that students' responses to the use of reward stamps tend to be positive. The interview findings reinforced the quantitative results, in which students showed increased confidence, courage in expressing and responding to opinions, mutual respect, and responsibility in completing tasks individually and in groups. In addition, reward stamps also increased students' motivation to learn because students felt appreciated for their efforts. Thus, the application of reward stamps showed a positive contribution in increasing student participation and supporting the creation of a more active and enjoyable English learning atmosphere.